Evaluation of INDUSCHIP-1 and selected low-density SNP panel for imputation to higher density in Gir dairy cattle of Gujarat - THAKKAR, R S; NAYEE, N G; VATALIYA, P H (The Indian Journal of Animal Sciences, 2021)
Application of Genomic Selection among other selection methods mainly depends upon the cost of genotyping, as cheaper the cost more animals can be genotyped to increase reference population size. Imputation approaches have been useful in reducing the cost. Imputation strategies and GS have been comprehensively studied in several taurine dairy cattle populations but very limited information is available on Bos Indicus populations. Factors that affect the efficiency of imputation are population structure, linkage disequilibrium between markers, and marker density in target and reference SPN panels. For present study, INDUSCHIP-1, a customized Illumina bovine microarray chip for indigenous cattle breeds, designed by NDDB, Anand was used for genotyping Gir cattle in India. The objective of the study is to evaluate the performance of INDUSCHIP-1 for imputation to Illumina BovineHD and also to select an LD SNP panel useful to impute at INDUSCHIP-1 level in Gir cattle. A fivefold cross validation by masking genotypes of animals to keep either INDUSCHIP-1 SNPs or LD SNPs and imputing to either HD level or at INDUSCHIP-1 level respectively, was performed. Population-based imputation algorithm BEAGLE was used without including pedigree information. Imputation accuracies evaluated as concordance level (allele correct rate expressed in percentage). All imputation accuracy, represented as % concordance between actual genotypes and imputed genotypes were showed as an average of five replicates for each chromosome. Mean concordance of 92.33% was observed when INDUSCHIP-1 genotypes were imputed at Illumina HD 777K level. The use of INDUSCHIP-1 as a HD Panel resulted in the accuracy of 88.42%. SNP selection criteria used for LD panel in the present study was very simple and seems effective. Distribution of polymorphic SNPs along the length of chromosomes and across all the chromosomes showed that this custom selected panel is a promising option for developing LD genotyping chip for Gir cattle.